Relationship Of Knowledge, Attitude, And Practice To Incidence Of Hepatitis A Virus Infection In Nursing Students In Jember - Hendra Dwi Cahyono; Ina Martiana (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2021)
Introduction: Hepatitis A virus (HAV) can cause inflammation in the liver. Indonesia is one of the countries with a high prevalence rate of hepatitis. The hepatitis A outbreak is an indicator of the lack of student’s concern in maintaining the food, drinks, or environment hygiene. Objective: The aim of the study was to determine the relationship between knowledge, attitude, and practice towards incidence of hepatitis A virus infection in nursing students. Methods: This research was a quantitative study with a descriptive analytical correlation design using a cross-sectional approach. The sampling technique used cluster sampling and 200 participants were obtained from nursing students in several colleges in Jember. The data collection process used an online google form for the questionnaires, because of the pandemic situation. The data analysis was carried out in univariate and bivariate analysis using Chi-square test. Results: The research results showed that there was a relationship between knowledge with incidence of hepatitis A infection which is significantly associated with alpha of 0.046 (<0.05) and OR of 1.140. There was no relationship between attitude and incidence of hepatitis A infection with alpha = 0.489 (> 0.05), as well as the relationship between practice and incidence of hepatitis A infection (p=0.489). High knowledge level has an important role in preventing the hepatitis A infection risk. Conclusion: Student’s attitude and practice are not significantly associated, because even the nursing students knew what to do for prevention of infection risk, they still didn’t do it in their daily activity.